The anatomical site of perforation peritonitis and their microbiological profile: a cross-sectional study - P., Lohith; Jindal, R. K.; Ghuliani, Deepak; P., Rajshekar (International Surgery Journal, 2020)
Background: Initiation of early appropriate antibiotic therapy influences the outcome of perforation peritonitis, which otherwise is delayed till culture reports are available. The knowledge of microbial profile and sensitivity of peritoneal fluid culture with respect to the anatomical site of perforation peritonitis will help in initiation of early appropriate antibiotic therapy in the post-operative period. Methods: A cross-sectional study conducted from January 2017 to December 2017 where intraoperative peritoneal fluid sample in patients of perforation peritonitis was subjected to culture (aerobic and anaerobic) and sensitivity and results analysed with respect to anatomical site of perforation. Results: 50 patients were studied. The most common site of perforation was ileum (32%) followed by appendix (18%) and stomach (18%). In aerobic culture, the culture positivity rate was highest in colonic perforation (100%) and least in gastric perforation (44.4%). The most common organism isolated in all sites of perforation peritonitis was E. coli followed by Klebsiella spp. In anaerobic culture, although facultative anaerobes were isolated, no strict anaerobe was isolated. The most sensitive antibiotics covering all isolated organisms were gentamycin (p=0.006), colistin (p=0.018), piperacillin and tazobactum (p=0.022). Conclusions: The predominant differential normal flora according to site of gastrointestinal tract was not reflected in the peritoneal fluid culture of patients with perforation peritonitis and E. coli was the most common organism isolated in all sites of perforation peritonitis. The antibiotic sensitivity profile showed the increasing resistance against third generation cephalosporins. Aminoglycosides, piperacillin and tazobactum, meropenem and colistin showed a significant antimicrobial activity against organisms isolated from cases of perforation peritonitis.